Respuesta :

Y/2+x
2/2+1
1+1
2
Hope this helps
GENERAL OUT

y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2